Towards Policy Recommendation: Curriculum Relevance, Employment Skills, and Competence Among Graduates of Doctor of Education Program in Isabela State University - Guzman, Rodel B. (Innovare Journal of Education, 2025)
The graduates of any higher education institution are the best indicator of their actual performance. Hence, the performance of the graduates can be best used for the improvement of any graduate program. The study was conducted to trace the graduates of the Doctor of Education program and to assess the relevance of its curriculum and the employment skills and competence of the graduates. The study found that most of the participants were very satisfied with their present jobs. Also, they assessed that the program and its various areas are relevant and adequate to the present needs of the industry. Interestingly, they characterize the program with faculty who have basic and compressive knowledge and skills in their field of specialization, applying various pedagogical techniques to improve classroom management and practice professional and ethical teaching standards. They also revealed that they develop employment skills and abilities such as multitasking, smooth relationships with peers and supervisors, problem identification and offering of novel solutions, and communication skills. However, it is recommended that the program management devise mechanisms to improve ICT, entrepreneurial, and extension skills among its graduates.